Methods and means of synthesis and generation of signals – physical carriers of data in modern information and communication systems - Горбенко, І.Д.; Семенко, Є.А.; Замула, О.А. (Radiotekhnika, 2020)
The functioning of a number of modern information and communication systems (ICS) is carried out under conditions of external and internal influences caused, on the one hand, by the action of natural interference, interference from other radio systems operating at close frequencies or in a common part of the frequency range, on the other hand , interference created by counteraction stations for the purpose of electronic suppression of existing systems. Increasingly stringent requirements are imposed on the ICS, especially for critical purposes, to ensure the efficiency of their functioning: the reliability and rate of information transfer, survivability, noise immunity, information security. In such conditions, the availability and use of secure information and communication systems is of particular importance. Under the security of systems is understood, first of all, their ability to provide the necessary indicators for noise immunity, imitation resistance, information, energy and structural secrecy, information transfer rate, frequency and energy efficiency. The need to use secure radio channels forces researchers to look in a new way, both at the modes of functioning of secure radio channels, and at the aspects of the formation and use of complex signals – physical data carriers for such systems. The paper presents conceptual provisions for the construction of secure ICS, which determine the need for a system classification and unification of information flows to solve the problems of information formation and processing in ICS, systematization of models, methods, hardware and software for their implementation. The principles of building new technologies in the field of ICS should cover the entire spectrum of information transformations in a complex, from a source to a consumer, and should be based not only on the effective transfer of information, but also on ensuring secrecy, electromagnetic and other compatibility, ecology, information security, protection from imposing (introduction into the system) of erroneous data and so on. It is shown that one of the complex problems of creating protected ICS is the synthesis of a system of signals – physical data carriers. The paper gives the analysis of a number of signal systems (OFDM – signals, signals with linear frequency modulation (LFM), complex nonlinear discrete signals), the use of which makes it possible to improve the efficiency indicators of modern ICS (reception noise immunity, information security, secrecy of functioning, protection from the introduction (imposition) of false messages, falsification of messages, ensuring data integrity, resistance to intersymbol interference, information capacity of the system with limited bandwidth, data transmission speed, etc.). In this paper, based on the study of the algebraic structure of systems of nonlinear parametric inequalities, the problem of synthesizing one of the new classes of complex nonlinear discrete signals with given correlation, ensemble and structural properties, cryptographic signals, is formulated and solved in a general form. The principles of construction and general characteristics of the created software and hardware complex for the synthesis, study of properties, generation, processing and testing of mathematical models of a number of classes of signals – physical data carriers in modern ICS.